2019
DOI: 10.4022/jafib.2110
|View full text |Cite
|
Sign up to set email alerts
|

Protecting the esophagus from thermal injury during radiofrequency ablation with an esophageal cooling device.

Abstract: Purpose: We sought to quantify the capabilities of a commercially available cooling device to protect the esophagus from RF injury in an animal model and develop a mathematical model to describe the system and provide a framework from which to advance this technology.Methods: A series of ablations (10 W, duration 30-45 seconds) were performed directly on exposed swine esophagus. Control ablations were performed with static 37°C water, and treatment ablations were performed with water (range 5°C-37°C) circulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 24 publications
1
11
0
Order By: Relevance
“…allowed a significant decrease in the percentage of damaged esophagus, where values of a maximum of 60% were seen in the control case without the use of protection to values of 0% in the protected cases using PEC. This reduction in esophageal injury aligns well with what has been seen with the use of PEC in RF ablation, both in preclinical and mathematical models 6,10,30,31 as well as in published clinical data. 32,33 Although the simplified geometric model has inherent limitations, recent clinical data have been presented with findings suggestive of a beneficial clinical effect from cooling during laser ablation, albeit without having a histopathological correlation on tissue effects.…”
Section: Discussionsupporting
confidence: 84%
“…allowed a significant decrease in the percentage of damaged esophagus, where values of a maximum of 60% were seen in the control case without the use of protection to values of 0% in the protected cases using PEC. This reduction in esophageal injury aligns well with what has been seen with the use of PEC in RF ablation, both in preclinical and mathematical models 6,10,30,31 as well as in published clinical data. 32,33 Although the simplified geometric model has inherent limitations, recent clinical data have been presented with findings suggestive of a beneficial clinical effect from cooling during laser ablation, albeit without having a histopathological correlation on tissue effects.…”
Section: Discussionsupporting
confidence: 84%
“…Preclinical data as well as mathematical modeling support the findings of a significant effect size, with a dose-response effect of coolant temperature shown in a large animal model,[24] and a significant reduction of lethal isotherm formation in the esophagus shown with mathematical models. [33, 36] Although randomized clinical studies have shown reductions in severe esophageal lesions with active esophageal cooling,[31, 37, 38] the effect sizes seen were not such that the findings of no AEF in our large population sample would be expected.…”
Section: Discussionmentioning
confidence: 68%
“…[21][22][23] Active esophageal cooling using a dedicated esophageal cooling device is a newer technique that has shown benefits in preclinical studies, mathematical modeling, and clinical studies. [24][25][26][27][28][29][30][31][32][33][34] An international multicenter randomized controlled trial is currently underway (NCT04577859), but this study relies on the surrogate endpoint of endoscopically detected esophageal lesion (EDEL) reduction. Because an event rate of <1% requires an extremely large sample size, no study to date has evaluated the effectiveness of any strategy in reducing AEFs.…”
Section: Introductionmentioning
confidence: 99%
“… 7 12 The use of high-power, short-duration ablation and the development of an ablation index may offer further safety improvements, but benefits to date in reducing esophageal injury in formal studies using objective endpoints (either magnetic resonance imaging– or endoscopy-proven esophageal injury) remain unclear. 41 , 42 On the other hand, currently available technology that provides active esophageal cooling has suggested benefits in multiple pre-clinical and clinical studies, 11 , 12 , 20 22 , 43 , 44 with two pilot RCTs and one confirmatory RCT demonstrating significant reductions in esophageal injury. 20 22 Procedural efficiency improvements in the form of reduced fluoroscopy requirements may add another benefit to this approach.…”
Section: Discussionmentioning
confidence: 99%
“…Actively cooling the esophagus during RF ablation has been reported to have several additional benefits, including improved procedural efficiency (allowing point-to-point ablation to occur without interruption from LET monitoring alarms), improved transmurality of lesions, and reduced fluoroscopy requirements. 11 , 12 , 25 – 29 Reduction of fluoroscopy usage is of increasing interest, as career-long radiation exposure to clinicians can result in higher lifetime risks of cataracts, stroke, atherosclerosis, and brain cancer. 30 …”
Section: Introductionmentioning
confidence: 99%